An evaluation of energy and carbon budgets in diverse cropping systems for sustainable diversification of rainfed uplands in India's eastern hill and plateau region - Pan, Rabi Sankar; Mali, Santosh S.; Kumar, Rakesh; Naik, Sushanta Kumar; Upadhyay, Pravin Kumar; Shinde, Reshma; Jha, Bal Krishna; Jeet, Pawan; Das, Anup (Frontiers in Sustainable Food Systems, 2024)
With increasing cost and use of energy in agriculture, the traditional practice of monocropping of rice in upland is neither sustainable nor eco-friendly. It is necessary to identify the crop diversification options with high energy efficiency, productivity, and low global warming potential (GWP). In this experiment, an inclusive system analysis was accomplished for three years (2016-2019) for five mono-cropping production (MCP) systems namely rice (R), finger millet (FM), black gram (BG), horse gram (HG), pigeon pea (PP) and four intercropped systems viz. R+BG, R+HG, FM+ BG and FM + HG. The key objective was to evaluate the flow of energy, carbon balance and GWP of these varied production systems. Puddled rice was recorded as energy exhaustive crop (27803 MJ ha -1 ), while horse gram noted the lowest energy use (26537 MJ ha -1 ). The total energy output from pigeon pea (130312 MJ ha -1 ) and diversified intercropped systems (142135 MJ ha -1 ) was 65.3 and 80.3% higher over mono-cultured systems. Rice and rice based intercropping production systems showed higher carbon footprints (1264 to 1392 kg CO2 eq. ha -1 ). Results showed that R+BG and R+HG were the most energy efficient production systems having higher energy ratio (5.8 and 6.0), higher carbon efficiency (7.41 and 8.24) and carbon sustainability index (6.41 and 7.24) as against 3.30, 3.61 and 2.61 observed under sole cropping production systems. On an average, rice and rice-based production systems had 7.4 times higher GWP over other production system. In productivity terms, pigeon pea and FM+HG had higher rice equivalent yield of 8.81 and 5.79 t ha -1 and benefit-cost ratio of 2.29 and 1.87, respectively. Thus, the present study suggests that pigeon pea and finger millet-based intercropping systems was the most appropriate crop diversification options for rainfed upland agro-ecosystem of eastern region of India.